Development of traction features in sprint spikes using SLS nylon sole units - Vinet, A.; Caine, M. (Procedia Engineering, 2010)
A novel method for incorporating traction features within sprint shoe sole units using selective laser sintering (SLS) was investigated. A bespoke test fixture for measuring traction between track surface and sole unit was developed and is described here. The traction properties of both commercially available and SLS sprint shoes were evaluated. With respect to the SLS sole units the evaluation focused upon whether or not they met the minimum traction requirements deemed necessary for sprinting. The potential to create a fully functional sprint shoe sole unit using additive manufacturing technologies is discussed.